Magia e superstizione: viaggio nel tempo - Marina D’Agati (Quaderni di Sociologia, 2009)
Michael D. Bailey’s Magia e superstizione in Europa dall’Antichità ai giorni nostri (Magic and Superstition in Europe: A Concise History from Antiquity to the Present) is a useful work for a wide audience. Based on a wide scholarship of the history of magic and witchcraft, it gives readers a comparative perspective on how different Western societies viewed and categorized magic and superstition, and how magical traditions changed and adapted to different historical conditions. Bailey looks at the reactions of society to them, almost always suspicion, prosecution and persecution. Prudently declining to give abstract definitions of magic and superstition, he allows them to appear as categories of separation and refusal in many different historical contexts. Bailey’s analysis covers two millennia: it begins in the depths of antiquity and proceeds to the twenty-first century. The focus is on Europe in the medieval and early modern eras, although sections do cover the ancient Near East, classical Greece and Rome, and the spread of magical systems – particularly modern witchcraft or Wicca – from Europe to the United States. Although conceptions of magic have changed over time, Bailey shows that magic has always been, and continues to be, an important aspect of European history. Particularly, he explains how magic has almost always served as a boundary marker separating socially acceptable actions from illicit ones, and more generally the known and understood from the unknown and occult.